Analisis Kompetensi Pedagogik Guru Biologi SMA Se-Kota Binjai - Siregar, Mariana; Harahap, Fauziyah; Sipahutar, Herbet (Jurnal Pendidikan Biologi, 2016)
The research was aim to know pedagogic competence teachersâ and factors relating to the competence of teachers. The population in this study are all biology teachers at 20 schools. The research sample as many as 34 teachers of biology. Data was collected by observation sheet, assessment lesson plan sheet, teacher questionnaire and data analyze were qualitative descriptive.The result revealed teacher pedagogic competence in arrange lesson plan was 11 persons (32.35%) categorized very good, 23 persons (67,65%) is good and the total average value 80,32 is good. Learning performance was 14 persons (41,18%) categorized very good and 20 persons (58,82%) is good and the total average value 80,68 is good.Factors that influence the pedagogical competence of teachers is level education background with compile lesson plan was 0.037, frequency certification acceptance was 0.025. An frequency activity of MGMP with learning performance was 0.012.